Transcultural Nursing Analysis in The Concept of Health Tourism : A Literature Review - Agustin, Leni; Rosyidi , Kholid; Riskika, Siti; Dwi Agustin, Yuana; Wicaksi, Damon (Universitas Bondowoso, 2022)
Background: Health tourism is a topic that is starting to be looked at in various parts of the world. The increase in the expectations of health tourists for the quality of health services certainly also has an impact on increasingly quality nursing care services for various clients from abroad. Nurses are required to handle the increasing number of visitors and migrants from abroad due to this globalization. This certainly has an impact on cultural factors which are a very important component of nursing competence where nurses are increasingly required to be able to carry out appropriate and appropriate nursing care to clients of foreign nationals. This study aims to describe health tourism and transcultural nursing concepts from the perspective of nurses and to find out how they interpret them. Methods: This literature uses inclusion and exclusion criteria using article data sources obtained and reviewed from the Google Scholar, PubMed and Willley Library databases. Results: The score obtained on the nurse's cultural sensitivity scale is a low average, cultural sensitivity also has no correlation with gender, marital status, age, educational level, professional title and background of transcultural nursing training. The cultural competency scores were significantly higher due to work experience treating foreign patients. Conclusion: Lack of language knowledge and experience of foreign cultures is an obstacle for nurses in caring for foreign patients. Improving foreign language skills, skills and work experience treating foreign patients is absolutely necessary in the context of meeting the needs for health tourism services.